Hepatitis B core-related antigen (HBcrAg) levels in the natural history of hepatitis B virus infection in a large European cohort predominantly infected with genotypes A and D. (June 2015) - Maasoumy, B.; Wiegand, S.B.; Jaroszewicz, J.; Bremer, B.; Lehmann, P.; Deterding, K.; Taranta, A.; Manns, M.P.; Wedemeyer, H.; Glebe, D.; Cornberg, M.
Abstract: Hepatitis B core-related antigen (HBcrAg) has been suggested as an additional marker of hepatitis B virus (HBV) infection. HBcrAg combines the antigenic reactivity resulting from denatured hepatitis B e antigen (HBeAg), HBV core antigen and an artificial core-related protein (p22cr). In Asian patients, high levels of HBcrAg have been suggested to be an independent risk factor for hepatocellular carcinoma, while low levels could guide safe cessation of treatment with nucleos(t)ide analogues. We here studied HBcrAg levels in different phases of HBV infection in a large European cohort predominantly infected with genotypes A and D: HBeAg-positive immune tolerance ( n = 30), HBeAg-positive immune clearance (IC) ( n = 60), HBeAg-negative hepatitis (ENH) ( n = 50), HBeAg-negative inactive/quiescent carrier phase (c) ( n = 109) and acute hepatitis B ( n = 8). Median HBcrAg levels were high in the immune tolerance and immune clearance phases (8.41 and 8.11 log U/mL, respectively), lower in ENH subjects (4.82 log U/mL) but only 2.00 log U/mL in ENQ subjects. Correlation between HBcrAg and HBV DNA varied among the different phases of HBV infection, while HBcrAg moderately correlated with hepatitis B surface antigen in all phases. ENQ patients had HBcrAg levels <3 log U/mL in 79%, in contrast to only 12% in the ENH group. HBcrAg levels vary significantly during the different phases of HBV infection. HBcrAg may serve as valuable marker for virus replication and reflect the transcriptional activity of intrahepatic cccDNA. In HBeAg-negative patients, HBcrAg may help to distinguish between inactive carriers (ENQ) and those with active disease (ENH).